CASE STUDY OF FALLOPIAN TUBAL BLOCK WITH DHANVANTARAM TAILA UTTARAVASTI AND YONIPICHU - Pushpalatha, *B.; Sharma, Sushueela; Bharathi, K. (International Journal of Ayurveda and Pharma Research, 2016)
Inability of a couple to achieve conception after one year of unprotected coitus is defined as infertility. Fecundability starts to decline from early thirties and accelerates during the late thirties and early forties. Achievement of conception depends on the fertility capacity of both the male and female partner; male is directly responsible in around 30% of cases, female in 30% and both are responsible for 30% of cases, and in the remaining 10% of cases cause remains unexplained. In the existing modern system of medicine, there is no proper intervention available to clear the tubal block. In Ayurveda, Uttaravasti and Yonipichu like direct solutions are available to deliver the drug in-situ in the uterus. Present study is reporting of a case of fallopian tubal block treated with Dhanvantaram oil Uttaravasti as well as Yonipichu (vaginal tampon). Unilateral tubal block was successfully cured with this trail drug and drug delivery methods.